Peranan Koperasi Wanita Serba Usaha Setia Budi Wanita Jawa Timur Dalam Memberikan Pinjaman LPDB Kepada Wirausaha di Malang - Celita Dwita Ardyani (Jurnal Ekonomi dan Studi Pembangunan, 2015)
In an effort to encourage the development of SMEs in Indonesia is required funding one of which is cooperative. The background of this study was to determine the effect LPDB loans granted by the cooperative to members who need loan funds In this study the role of cooperatives as conduits LPDB loan is needed to simplify the process of lending LPDB. Subjects in this study is the Women's Cooperative “Setia Budi Wanita” East Java and its object is the independent variable in this study that LPDB loans (Revolving Fund Management Institution). This research is a qualitative descriptive study. Data collection techniques used in this research is the snowball sampling technique used in determining the subject to be interviewed. These results indicate that the role of Women's Cooperative Business Solutions Business “Setia Budi Wanita” East Java in lending LPDB (Institute of Management Revolving Fund) had a positive effect for cooperative members who borrow loans LPDB (Institute of Management Revolving Fund), especially for the self-employed and the factors driving and obstacles in lending LPDB.Keywords: Cooperative,  LPDB  (Institute  of  Management  Revolving  Fund), SMEs